Origins, history and relationships of indigenous African cattle - Hanotte, Olivier H.; Rege, J.E.O. (2000)
With some 180 million head. comprising more than 150 different breeds or populations of taurine Bos taurus, indicine B. indicus and intermediate origin, the African continent is home to an enormous reservoir of cattle biodiversity. Recent archaeological findings are providing new insights into the origin and migration of cattle populations into Africa. They indicate that cattle pastoralism preceded cereal agriculture in most of Africa and that cattle were possibly domesticated within the continent from the African wild relative auroch B. primigenius. The early sites with evidences of domesticated African cattle are Bir Kiseiba and Nabta Playa in South Egypt (11000 BP - 6000 BP). Extensive molecular genetics studies at the International Livestock Research Institute (Kenya) and at Trinity College Dublin (Ireland) support an indigenous origin for African cattle. Moreover, autosomal and Y specific microsatellite analyses have revealed in details the genetic relationships among the present day African breeds. Very little to no Asian zebu, Middle East or European taurine influences were detected amongst the West African taurine living within the tsetse fly zone. A major Asian zebu influence, which probably started around the seventh and eighth century AD, is clearly visible amongst the cattle populations of Eastern Africa and the Sahel. These populations are the result of interbreeding between African indigenous taurine and zebu of Asian origin. The predominantly taurine genetic background of the southern African sanga supports the archaeological view of an early arrival of cattle in the southern part of the continent before the major zebu influence in the Horn of Africa. The origin and history of present day African indigenous cattle demonstrate their unique genetic background. It strongly argues for their conservation and sustainable utilisation for future livestock production in Africa and elsewhere.